Forced convective heat transfer and fluid flow past a rotating hand-shaped former for improving rubber glove curing - Kittipos Loksupapaiboon; Chakrit Suvanjumrat (Case Studies in Thermal Engineering, 2023)
In the present pandemic, rubber gloves have been extensively used in the medical and healthcare fields. However, the increase in production capability to meet the accelerating demand deteriorated the curing process of the rubber gloves, which led to poor quality gloves. In this study, forced convective heat transfer around a rotating hand-shaped former was analyzed using computational fluid dynamics (CFD) to improve the rubber glove curing process. To this end, a 3-D scanner modeled a typical hand-shaped former for the moving reference frame in the CFD model. Further, an SST k-ω turbulence model and its wall functions were applied with OpenFOAM software. The constant dimensionless rotation rate (α) was varied from 0 to 5 in the Re∞ range 1583–15,837, which is same as that in manufacturing process. The simulation results agreed well with the experimental data. The results confirmed that the convective heat transfer of the individual section and entire body varied according to variables Re∞ and α. The rotation rate affected the heat transfer in the finger gaps. This former segment was affected by forced convective heat transfer, as justified by the analysis of variance. Therefore, a novel average Nusselt number governing the heat transfer around the middle finger was proposed. This equation depends on the former geometry, rotation rate, and airflow velocity, which are significant for setting up the curing process and rapidly improving rubber gloves.